ANALISIS PENGARUH RASIO PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN YANG TERCANTUM DALAM INDEKS LQ45 - Abdullah, Haidar; Asakdiyah, Salamatun (Jurnal Fokus Manajemen Bisnis, 2015)
This study aimed to examine the effect of profitability ratio on stock price of companies  listed  in  LQ45  index  in  Indonesia  Stock  Exchange  (BEI).  Profitability ratios here in include Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE),  and Eearning Per Share  (EPS). This study  was conducted to assess the financial performance of the company to generate earnings from an investment.This study uses secondary data. The population in this study is the companies included in the LQ45 index from  2010-2013 amounting to 78. The total sample is 16 companies  belonging  to  and  representing  several  sectors  including  the  financial sector companies, automotive, property, plantation, infrastructure, mining, industrial cement, as well as the consumer goods  industry are consistently incorporated in the four observation period 2010-2013 in LQ45 index that has been determined through purposive  sampling  method.  Method  of  hypothesis  testing  using  Classical Assumption  Test,  Regression,  t  test,  F  test,  and  the  coefficient  of  determination  by alpha (α) of 5%.Regression analysis showed that in partial Net Profit Margin (NPM), Return on Assets (ROA) and Return On Equity (ROE) significantly influence the stock price while the variable Eearning Per Share (EPS) has no significant effect on stock price. Simultaneously  all  variables  Net  Profit  Margin  (NPM),  Return  on  Assets  (ROA), Return on Equity (ROE), and Eearning Per Share (EPS) have a significant effect on stock price. The value of coefficient of determination (R2) of  0.899, which means that the independent variable Net Profit Margin (NPM), Return on Assets (ROA), Return on Equity (ROE), and Eearning Per Share (EPS) is able to explain the variation of the dependent variable stock price by 89,9%, while the remaining 10.1 % is explained by other variables outside of the variables used in the study.